Thrombocytopenia in the first trimester predicts adverse pregnancy outcomes in obstetric antiphospholipid syndrome - Jin, Jiayang; Xu, Xue; Hou, Lei; Hou, Yuke; Li, Jing; Liang, Meiying; Li, Chun (Frontiers in Immunology, 2022)
Background: Thrombocytopenia is a common manifestation of antiphospholipid syndrome (APS), and is a main concern for bleeding on the standard treatment of low dose aspirin (LDA) and low molecular weight heparin (LMWH) in obstetric APS (OAPS). Objective: This study assesses the possible relationship between thrombocytopenia during the first trimester and adverse pregnancy outcomes (APOs) in OAPS patients. Methods: A case-control study was conducted at Peking University People’s Hospital, Beijing, China. The clinical, immunologic, and pregnancy outcomes of the OAPS patients were collected. Univariate and multivariate logistic regression analyses were applied to assess the relationship between APOs and thrombocytopenia in the first trimester. Results: A total of 115 participants were included in the analysis. Compared to the control group, thrombocytopenia in the first trimester was correlated with SGA (12.12% vs.31.25, p = 0.043), premature birth <37 weeks (16.16% vs 43.75%, p = 0.010) and intrauterine fetal death (2.02% vs 12.50%, p = 0.033). Thrombocytopenia in first-trimester independently increased the risk of preterm birth <37 weeks (OR = 5.40, 95% CI: 1.35-21.53, p = 0.02) after adjusting for demographic and laboratory factors. After adding medication adjustments, these factors above become insignificant (p > 0.05). Of note, the number of platelets increased after delivery in 14 thrombocytopenia patients with live fetuses (p = 0.03). Conclusion: This study demonstrates that thrombocytopenia in the first trimester increases the risks of preterm birth in women with APS. The effective OAPS treatments may improve pregnancy outcomes and not increase the risk of antepartum and postpartum hemorrhage.